AWARENESS AND TOBACCO DEPENDENCY LEVEL AMONG ADOLESCENT PATIENTS VISITING CESSATION CLINIC IN A DENTAL HOSPITAL - B, Revathi; Kanimozhi,; kumar.R, Pradeep; kumar, Kiran (International Journal of Psychosocial Rehabilitation, 2020)
Almost 7 million deaths occur per year worldwide due to tobacco addiction. Tobacco causes many oral health complications like tooth stain, periodontal diseases, oral lesions and oral cancer. Adolescents who smoke demonstrate the various smoking behaviors, but it is still unclear how dependence develops, manifests and is accurately measured. Hence, the aim of the study is to assess the awareness and to determine the tobacco dependency level among adolescent patients visiting cessation clinic in a dental hospital. The present study is a retrospective study. 86000 patient records were reviewed and analyzed from which 300 patients who were adolescents' tobacco users are included in this study. Age, gender, type of tobacco, duration and frequency of tobacco usage, Fagerstrom tobacco nicotine dependence was assessed. The data was tabulated and subjected to statistical analysis. The results depicted that 67.7% were smokers and smokeless tobacco was common among 32.2%. Males show the highest prevalence. Majority of them use less than 10 cigarettes per day. Peer pressure acts as a major encouraging factor followed by co-workers and family. More than 50% reported medium dependency level. Significant association was found between the number of years using tobacco and tobacco dependency level (p